Laparoscopic liver resection versus open liver resection for intrahepatic cholangiocarcinoma: 3-year outcomes of a cohort study with propensity score matching. (June 2020) - Kang, So Hyun; Choi, YoungRok; Lee, Woohyung; Ahn, Soyeon; Cho, Jai Young; Yoon, Yoo-Seok; Han, Ho-Seong
Abstract: Introduction: Laparoscopic liver resection(LLR) for intrahepatic cholangiocarcinoma is debatable due to technical challenges associated with major hepatectomy and lymph node dissection. This study aims to analyze the long-term outcomes with propensity score matching. Methods: Patients who underwent liver resection for intrahepatic cholangiocarcinoma from August 2004 to October 2015 were enrolled. Those who had combined hepatocellular-cholangiocarcinoma and palliative surgery were excluded. Medical records were reviewed for postoperative outcome, recurrence, and survival. The 3-year disease-free survival(DFS) and 3-year overall survival(OS) were set as the primary endpoint, and 3-year disease-specific survival, 1-year OS, 1-year DFS, operative outcome, and postoperative complications were secondary endpoints. Results: A total of 91 patients were enrolled with 61 in the open group and 30 in the laparoscopic group. Propensity score matching included 24 patients in both groups. In total, the 3-year OS was 81.2% in the open group and 76.7% in the laparoscopic group(p = 0.621). For 3-year DFS, open was 42.5% and laparoscopic was 65.6%(p = 0.122). Mean operation time for the open group was 343.2 ± 106.0 min and laparoscopic group was 375.2 ± 204.0 min(p = 0.426). Hospital stay was significantly shorter in the laparoscopic group(9.8 ± 5.1 days) than the open group(18.3 ± 14.7, p=<0.001). There was no difference in complication rate and 30-day readmission rate. Tumor size, nodularity, and presence of perineural invasion showed an independent association with the 3-year DFS in multivariate analysis. Conclusion: Laparoscopic liver resection for intrahepatic cholangiocarcinoma is technically feasible and safe, providing short-term benefits without increasing complications or affecting long-term survival. Highlights: The 3-year OS for the open and laparoscopic group was 81.2% and 76.7% respectively (p = 0.621). The 3-year DFS was 42.5% for the open group and 65.6% for the laparoscopic group (p = 0.122). There was no difference in survival between the open and laparoscopic groups.